2008
DOI: 10.1167/iovs.07-0559
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality of Life and Priorities of Patients with Glaucoma

Abstract: Assessments of quality of life using different methodologies have been shown to produce different outcomes with low intercorrelations between them. Only a minority of patients were prepared to trade time for a return to normal vision. Conjoint analysis showed two subgroups with different priorities. Severity of glaucoma influenced the relative importance of priorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
122
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(134 citation statements)
references
References 46 publications
4
122
0
6
Order By: Relevance
“…The EQ-5D 5 has been found to be insensitive to HRQoL in this population; studies using this measure found mean scores that did not differ substantially from their respective population norms. 28,29 Within this study, the mean EQ-5D value (0.77) was consistent with the values found in the literature of 0.80 29 and 0.76, 28 and with the average value of 0.78 for people aged 65-75 years 30 within the general population, which implies that the HRQoL of the average glaucoma patient is not severely affected. This would therefore have significant implications for resource allocation, as the treatment may only have a marginal effect on HRQoL.…”
Section: Discussionsupporting
confidence: 91%
“…The EQ-5D 5 has been found to be insensitive to HRQoL in this population; studies using this measure found mean scores that did not differ substantially from their respective population norms. 28,29 Within this study, the mean EQ-5D value (0.77) was consistent with the values found in the literature of 0.80 29 and 0.76, 28 and with the average value of 0.78 for people aged 65-75 years 30 within the general population, which implies that the HRQoL of the average glaucoma patient is not severely affected. This would therefore have significant implications for resource allocation, as the treatment may only have a marginal effect on HRQoL.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with glaucoma commonly report problems with reading [1][2][3][4][5], and studies of actual reading performance have confirmed that glaucoma, especially when in an advanced stage, impacts on reading performance [9][10][11]. The patients in our study had advanced VF defects and were, therefore, similar to those previously characterized to have poorer reading performance when compared to age-similar controls [9].…”
Section: Discussionsupporting
confidence: 62%
“…Difficulty with reading is a common complaint made by patients with glaucoma [1][2][3][4][5]. Studies measuring actual reading performance have revealed impaired reading speed in patients when reading small print [6] or passages of text presented at low contrast [7].…”
Section: Introductionmentioning
confidence: 99%
“…This observation is supported by those studies that have strikingly shown that less than one quarter of glaucoma patients were willing to trade any longevity for perfect vision in so-called time trade off experiments. 68 For many patients, the psychological strain of the diagnosis, side-effects of treatment, and fear of blindness might be more affecting than the impact of subtle levels of sight loss. The cleverly designed study of Odberg et al 69 from nearly 15 years ago highlighted that 80% of newly diagnosed patients reported serious levels of anxiety and depression because of their diagnosis, despite 83% self-reporting good or excellent vision, and half having no visual symptoms.…”
Section: Discussionmentioning
confidence: 99%